Informational and Computer Technologies in Education: Ways of Realization - Vasilyeva, Г.І.; Dosenko, Г.П. (Journal of Information Technologies in Education (ITE), 2008)
The article deals with practical aspects of realization of informational and communicational technologies in management as well as in educational and pedagogic process of secondary educational establishments. It grounds the necessity of introducing Internet resources in the educational process. The article describes the experience of Belozyorka region of Kherson oblast in introducing informational and communicational technologies.